Phonon Dispersion of Alkali Metals Using the TB-SMA Model of Cohesion - E.E., Aigbekaen; Okunzuwa, Samuel; Ejere, Arthur I. (European Scientific Journal, ESJ, 2019)
The determination of Phonon dispersion of alkali metals was unsuccessful using the parameter n=1/2 or 2/3 in the past two decades. In this study the parameter n has been consistently determined for the different alkali metals, the force constant has been determined up to the fourth next nearest neighbour. The result showed that the TB-SMA dispersion curves were in good agreement with experiment. This good agreement with experiment of the TB-SMA Phonons counters the prevailing notion in the literature that the TB-SMA model fails for alkali metals.